2011
DOI: 10.1002/ejoc.201001581
|View full text |Cite
|
Sign up to set email alerts
|

A Clean, Highly Efficient and One‐Pot Green Synthesis of Aryl/Alkyl/Heteroaryl‐Substituted Bis(6‐amino‐1,3‐dimethyluracil‐5‐yl)methanes in Water

Abstract: A highly efficient green synthesis of aryl/alkyl/heteroarylsubstituted bis(6-amino-1,3-dimethyluracil-5-yl)methanes by the condensation of 6-amino-1,3-dimethyluracil with aldehydes (aromatic, aliphatic and heterocyclic) in water at room

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 94 publications
2
19
0
1
Order By: Relevance
“…With the previously reported catalyst characterizations in hand [39], to begin with, reaction of 6,6′-diamino-1,1′,3,3′-tetramethyl-5,5′-(benzylidene)bis[pyrimidine-2,4 (1H, 3H)-dione] [36] ( 1a , 1 mmol) with formic acid (6 mmol) was chosen as the model reaction (Scheme 2). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the previously reported catalyst characterizations in hand [39], to begin with, reaction of 6,6′-diamino-1,1′,3,3′-tetramethyl-5,5′-(benzylidene)bis[pyrimidine-2,4 (1H, 3H)-dione] [36] ( 1a , 1 mmol) with formic acid (6 mmol) was chosen as the model reaction (Scheme 2). …”
Section: Resultsmentioning
confidence: 99%
“…Uracil derivatives also have several potent medicinal properties such as bronchodilators and anticancer [28, 29], antiallergic [30, 31], antiviral [32, 33], antihypertensive, and adenosine receptor antagonists [34, 35]. Recently, our research group reported a greener protocol for the synthesis of bisuracil derivatives [36]. Bisuracil and their analogues have also been isolated from marine sea hare Dolabella auricularia [37].…”
Section: Introductionmentioning
confidence: 99%
“…All of the alkyl-substituted bis(6-amino-1,3-dimethyluracil-5-yl)methanes were prepared according to a synthetically simple procedure (Scheme 1) [29]. 6-amino-1,3-dimethyluracil (10 mmol) was added to distilled water (250 mL) in a 500 mL round-bottomed flask, and the mixture was stirred until all the 6-amino-1,3-dimethyluracil had dissolved.…”
Section: Methodsmentioning
confidence: 99%
“…In the FTIR spectrum of the purified PVC sample after aging for 10 min (Fig. 4b), the salient absorption bands at approximately 3390 and 3230 cm -1 are assigned to the amine groups [29]. This feature indicates that OSU becomes chemically bonded to the degraded polymeric chains during the stabilization process.…”
Section: Mechanism For the Stabilization Action Of The Prepared Compomentioning
confidence: 96%
“…1E) and bis-uracils (Fig. 1F) are known to exhibit antibacterial as well as anticancer activities [43][44][45][46][47]. Indoles are conventionally not regarded as active methylene compounds.…”
Section: Introductionmentioning
confidence: 99%